Potential of Incorporation of Antimicrobial Plant Phenolics Into Polyolefin-Based Food Contact Materials to Produce Active Packaging by Melt-Blending: Proof of Concept With Isobutyl-4-Hydroxybenzoate - Cottaz, Amandine; Bouarab, Lynda; De Clercq, Justine; Oulahal, Nadia; Degraeve, Pascal; Joly, Catherine (Frontiers in Chemistry, 2019)
There is an increasing interest for active food packaging incorporated with natural antimicrobial agents rather than synthetic preservatives. However, most of plastics for direct contact with food are made of polyolefins, usually processed by extrusion, injection or blow-molding methods while most of natural antimicrobial molecules are thermolabile compounds (e. g. essential oils). Therefore, addition of plant phenolics (with low volatility) to different polyolefins might be promising to design active controlled release packaging processed by usual plastic compounding and used for direct contact with food products. Therefore, up to 2% (wt/wt) of isobutyl-4-hydroxybenzoate (IBHB) was mixed with 3 polyolefins: EVA (poly(ethylene-co-vinyl acetate), LLDPE (Linear Low Density Polyethylene) and PP (PolyPropylene) by melt-blending from 75°C to 170°C and then pelletized in order to prepare heat-pressed films. IBHB was chosen as an antibacterial phenolic active model molecule against Staphylococcus aureus to challenge the entire processing. Antibacterial activity of films against S. aureus (procedure adapted from ISO 22196 standard) were 4, 6, and 1 decimal reductions in 24 h for EVA, LLDPE, and PP films, respectively, demonstrating the preservation of the antibacterial activity after melt processing. For food contact materials, the efficacy of antimicrobial packaging depends on the release of the antimicrobial molecules. Therefore, the 3 types of films were placed at 23°C in 95% (v/v) ethanol and the release rates of IBHB were monitored: 101±1%, 32±7%, and 72±9% at apparent equilibrium for EVA, LLDPE and PP films respectively. The apparent diffusion coefficients of IBHB in EVA and PP films were 2.8±0.3x10-12 and 4.0±1.0x10-16 m2.s-1. For LLDPE films, IBHB crystals were observed on the surface of films by SEM (Scanning Electron Microscopy): this blooming effect was due the partial incompatibility of IBHB in LLDPE and its fast diffusion out of the polymer matrix onto the film surface. In conclusion, none of these 3 materials was suitable for a relevant controlled release packaging targeting the preservation of fresh food, but a combination of 2 of them is promising by the design of a multilayer packaging: the release could result from permeation through an inner PE layer combined with an EVA one acting as a reservoir.